2018
DOI: 10.1080/02678292.2018.1468500
|View full text |Cite
|
Sign up to set email alerts
|

Mesomorphic properties of cyanobiphenyl dimers with a central malonate unit

Abstract: All chemicals were obtained from the supplier and used without further purification. Dry solvents were prepared by common laboratory methods. The eluents for chromatography petroleum ether (low-boiling) and ethyl acetate were distilled prior to use.Thinlayer chromatography silica gel 60 F254 glass plates (layer thickness of 0.20 mm on aluminium, pore size 60 Å) from the company Merck were used. Column chromatography

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
4
0
2
Order By: Relevance
“…Bununla birlikte, yönelimsel düzen parametresi sıcaklığa bağlıdır, moleküllerin dipolleri ve düzen parametresi konformasyonel dağılımdan etkilenmektedir [1][2][3][4][5][6]. Sıvı kristal bir malzemenin dielektrik özellikleri hem frekans ( ) hem de sıcaklığa ( ) bağlıdır [34][35][36][37][38][39][40]. Dielektrik geçirgenlik * ( , ) = '( , ) − "( , ) şeklindedir.…”
Section: Materyal Ve Yöntemunclassified
See 1 more Smart Citation
“…Bununla birlikte, yönelimsel düzen parametresi sıcaklığa bağlıdır, moleküllerin dipolleri ve düzen parametresi konformasyonel dağılımdan etkilenmektedir [1][2][3][4][5][6]. Sıvı kristal bir malzemenin dielektrik özellikleri hem frekans ( ) hem de sıcaklığa ( ) bağlıdır [34][35][36][37][38][39][40]. Dielektrik geçirgenlik * ( , ) = '( , ) − "( , ) şeklindedir.…”
Section: Materyal Ve Yöntemunclassified
“…Bu tür molekül yapısına sahip mezofazlar burulu-bükümlü (twist-bend) nematik fazı (Ntb) olarak adlandırılırlar. Bu yeni fazda moleküllerin kendileri etkin bir şekilde kiral olmamalarına rağmen yön vektörü dizilimi helikoidal (helicoidal) bir yapıdır [35][36][37][38][39]. Yön vektörü sarmal eksene göre eğilir ve kendiliğinden meydana gelen adım uzunluğu tipik olarak 10 nm civarındadır [35].…”
Section: Introductionunclassified
“…Column chromatography was conducted using silica gel (FUJIFILM Wako Pure Chemical Corporation, Wakogel ® 60N, 38-100 μm; Osaka, Japan) and thin layer chromatography (TLC) was performed on silica gel TLC plates (Merck, Silica gel 60F254; Kenilworth, NJ, USA). Based on the knowledge we acquired on the photophysical behavior of such fluorinated π-conjugated molecules, e.g., 1a, we envisioned that dyads 2a-f consisting of two fluorinated tolane-based luminophore 1a and an alkylene linkage as a spacer could take up a different molecular geometry depending on the linkage length, based on factors such as the odd-even effect [29][30][31][32]. Therefore, we constructed various molecular aggregated structures to display various photophysical behaviors.…”
Section: Generalmentioning
confidence: 99%
“…With deep investigations, interestingly, the PL behavior of 1a and the nonfluorinated analogue on the aromatic ring was found to change with an alteration of the molecular aggregated structures in the crystalline lattice; it was shown that fluorine atoms attached to an aromatic ring offering control over the molecular aggregated structure and photophysical behavior. Based on the knowledge we acquired on the photophysical behavior of such fluorinated πconjugated molecules, e.g., 1a, we envisioned that dyads 2a-f consisting of two fluorinated tolanebased luminophore 1a and an alkylene linkage as a spacer could take up a different molecular geometry depending on the linkage length, based on factors such as the odd-even effect [29][30][31][32]. Therefore, we constructed various molecular aggregated structures to display various photophysical behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid crystals with monotropic mesophase are especially used to obtain new eutectic liquid crystal mixtures with wide temperature range and liquid crystal with side chain discotic-columnar molecular structure [5][6][7][8]. However, monotropic liquid crystals are used to form some dimeric molecules, called twist-bend nematic phase, which consists of two mesogenic structures combined with a flexible separator [9][10][11][12][13]. The 4propoxy-biphenyl-4-carbonitrile (3OCB) monotropic nematic liquid crystal is a liquid crystal belonging to the 4-alkoxy-4-cyanobiphenyls (mOCBs).…”
Section: Introductionmentioning
confidence: 99%